Nature-based tourism motivations and visit profiles of domestic and international segments to a Japanese national park - Jones, Thomas E.; Nguyen, Minh-Hoang (Quaestiones Geographicae, 2021)
The rapid post-millennial internationalisation of Japan’s tourism sector and the influx of international visitors have quickly increased visitor motivations’ heterogeneity, thereby posing challenges for management. Given the lack of prior research, we aimed to identify nature-based tourism (NBT) push-factor motivation domains of visitors in a Japanese national park and segment domestic and international visitors based on their motivations, demographics and trip profiles. Primary data collection of 137 responses took place in November 2019 through an on-site self-administered questionnaire. From 11 push-factor statements, the principal component analysis yielded a four-factor solution: ‘enjoying nature with family or friends’, ‘improving physical health’, ‘discovering and learning’ and ‘escaping’. In addition, t-tests revealed significant differences between domestic and international visitors in three out of the four motivation dimensions. Underlying visitor profiles could explain some such differences. Despite the differences, both international and domestic visitors share similar motivations regarding ‘improving physical health’. These findings hint at the complexity of monitoring heterogeneous visitor segments within Japanese NBT. Despite increasing international visitors, there has been a lack of the necessary infrastructure and facilities to accommodate them. Thus, this study’s implications might help diversify NBT management strategies to deal with current shortcomings in Japan’s tourism sector.